Piston rings up to 200 mm diameter for reciprocating internal combustion engines. Designs, dimensions and designations for single piece rings. Keystone and half keystone compression rings. Specification for keystone rings Part 7.3.1, (1st May 1992) - British Standards Institution,
No abstract available